The Relationship Between Teachers' Distance Education Self-Efficacy, Job Satisfaction, and Professional Burnout - Bayram Gökbulut; Canan Öztürk (Uluslararası Türk Eğitim Bilimleri Dergisi)
The aim of this study is to reveal the relationships between teachers' self-efficacy perceptions towards distance education, job satisfaction, and professional burnout levels. The research was carried out with 206 teachers working in public schools in a province in the Western Black Sea Region. The data were collected using the Teachers' Self-Efficacy Belief Scale for Distance Education, Job Satisfaction Scale, and Professional Burnout Scale in the 2023-2024 academic year. As a result of the analysis of the data, it was seen that teachers' distance education self-efficacy and job satisfaction levels were above average, while their professional burnout levels were below average. No significant difference was found between teachers' self-efficacy perceptions towards distance education, job satisfaction and professional burnout levels, and gender and school type variables. No significant difference was found between teachers' self-efficacy perceptions towards distance education and professional burnout levels and professional seniority variable. There was a significant difference between job satisfaction and professional seniority, and this difference was in favor of teachers with higher professional seniority. While a positive low-level relationship was found between teachers' distance education self-efficacy perceptions and job satisfaction, no significant relationship was found between professional burnout. A negative relationship was found between teachers' job satisfaction and professional burnout levels. It is recommended to examine the relationships between the components of professional burnout and job satisfaction in this study and technology-based variables such as digital burnout and technostress.